Softening the Donor-Set: From [Cu(P^P)(N^N)][PF6] to [Cu(P^P)(N^S)][PF6] - Isaak Nohara; Alessandro Prescimone; Catherine E. Housecroft; Edwin C. Constable (Inorganics, 2019)
We report the synthesis and characterization of [Cu(P^P)(N^S)][PF6] complexes with P^P = bis(2-(diphenylphosphino)phenyl) ether (POP) or 4,5-bis(diphenylphosphino)-9,9- dimethylxanthene (xantphos) and N^S = 2-(iso-propylthio)pyridine (iPrSpy) or 2-(tert-butylthio)pyridine (tBuSpy). The single crystal structures of [Cu(POP)(iPrSPy)][PF6] and [Cu(POP)(tBuSPy)][PF6] have been determined and confirm a distorted tetrahedral copper(I) centre and chelating P^P and N^S ligands in each complex. Variable temperature (VT) 1H and 31P{1H} NMR spectroscopy reveals dynamic behavior with motion of the POP backbone in [Cu(POP)(iPrSPy)][PF6] and [Cu(POP)(tBuSPy)][PF6] frozen out at 238 K. VT NMR spectroscopic data including EXSY peaks in the ROESY spectrum of [Cu(xantphos)(tBuSPy)][PF6] at 198 K reveal that two conformers exist in an approximate ratio of 5:1. Replacing bpy by the N^S ligands shifts the Cu+/Cu2+ oxidation to a higher potential. The copper(I) compounds are weak emitters in the solid state with PLQY values of <2%. These values are similar to those for [Cu(POP)(bpy)][PF6] and [Cu(xantphos)(bpy)][PF6] in the solid state.